2020
DOI: 10.1111/tct.13181
|View full text |Cite
|
Sign up to set email alerts
|

Integrating handover curricula in medical school

Abstract: Background: Transitions of care are a patient-safety priority. Constructs such as SBAR (situation, background, assessment, recommendation) and I-PASS (illness severity, patient summary, action list, situation awareness, synthesis by receiver) have been used to teach the benefit of structured handovers and have demonstrated an impact in simulated and clinical environments. Despite this, there is still a lack of literature describing handover training for medical students that allows early and sustained knowledg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Given that these two elements have proven their usefulness in improving communication between caregivers (25),( 26), (27) and are probably not yet part of the habits of the HUG internal medicine department, it could be advantageous to introduce them explicitly into the training of the internists.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given that these two elements have proven their usefulness in improving communication between caregivers (25),( 26), (27) and are probably not yet part of the habits of the HUG internal medicine department, it could be advantageous to introduce them explicitly into the training of the internists.…”
Section: Discussionmentioning
confidence: 99%
“…have shown (27),(28), (29) without making them longer. Future studies will be needed to assess the impact of our recommendation.…”
Section: Abbreviationsmentioning
confidence: 99%
“…Since the completion of our prior pediatric I-PASS Study, literature has emerged suggesting that I-PASS might be adapted for use by nurses 29 and medical students, 6,30 as well as psychiatrists, 31 Emergency Department physicians, 32,33 and other provider [34][35][36] or handoff types. 37,38 While these studies reported improved outcomes and handoff quality following implementation, they typically had a less comprehensive implementation approach, reported fewer outcomes without a focus on process measures as well as adverse events and were typically conducted in only one or two units at a time within a single institution.…”
Section: Subgroup Analysesmentioning
confidence: 99%
“…Emphasising teaching handover skills in medical school: A recent graduate's perspective I read with interest the article by Sheng et al 1 , which highlighted the importance of teaching handover skills at medical school. As a newly…”
Section: E T T E R T O T H E E D I T O Rmentioning
confidence: 99%